Photometric Calibrations of M-dwarf Metallicity with Markov Chain Monte Carlo and Bayesian Inference - C. Duque-Arribas; D. Montes; H. M. Tabernero; J. A. Caballero; J. Gorgas; E. Marfil (The Astrophysical Journal, 2023)
Knowledge of stellar atmospheric parameters ( T _eff , $logg$ , [Fe/H]) of M dwarfs can be used to constrain both theoretical stellar models and Galactic chemical evolutionary models, and guide exoplanet searches, but their determination is difficult due to the complexity of the spectra of their cool atmospheres. In our ongoing effort to characterize M dwarfs, and in particular their chemical composition, we carried out multiband photometric calibrations of metallicity for early- and intermediate-type M dwarfs. The third Gaia data release provides high-precision astrometry and three-band photometry. This information, combined with the 2MASS and CatWISE2020 infrared photometric surveys and a sample of 4919 M dwarfs with metallicity values determined with high-resolution spectroscopy by The Cannon and APOGEE spectra, allowed us to study the effect of the metallicity in color–color and color–magnitude diagrams. We divided this sample into two subsamples: we used 1000 stars to train the calibrations with Bayesian statistics and Markov Chain Monte Carlo techniques, and the remaining 3919 stars to check the accuracy of the estimations. We derived several photometric calibrations of metallicity applicable to M dwarfs in the range of −0.45 ≤ [Fe/H] ≤ + 0.45 dex and spectral types down to M5.0 V that yield uncertainties down to the 0.10 dex level. Lastly, we compared our results with other photometric estimations published in the literature for an additional sample of 46 M dwarfs in wide binary systems with FGK-type primary stars and found a great predictive performance.